Economic and production consequences of current forest management in mature Scots pine (Pinus sylvestris) forests in Lithuania - Šatinskas, Rokas (2019)
Forestry takes up a major part in the economy of Northern Europe countries. The aim of this work is to evaluate the economic and production consequences in Scots pine (Pinus sylvestris) stands in Lithuania based on the data of the National Forest Inventory (NFI). Scots pine stands cover the biggest area of Lithuanian forests. It this thesis, it was decided to evaluate only the thinnings of the IV forest group (commercial forests) where the economical profit is the major aim.